Dual-targeted ping-pong CAR T cells: Leveraging peripheral expansion to improve solid tumor immunotherapy - Amanda V. Finck; Ziming Wang; Donna Gonzales; Nils Wellhausen; Sofía Castelli; Esha Banerjee; M. Angela Aznar; Regina M. Young; Carl H. June (Proceedings of the National Academy of Sciences, 2025)
Clinical responses to CD19-directed CAR T cell therapy in B cell malignancies are strongly associated with robust CAR T cell expansion in the peripheral blood. In contrast, CAR T cells targeting solid tumors do not encounter cognate antigen in the periphery, resulting in limited expansion and subtherapeutic peak concentrations. To overcome this, we engineered dual-targeted and dual-costimulated CAR T cells (CD19/28ζ-M5BBζ) that recognize CD19+ B cells, thereby promoting peripheral expansion and increasing the pool of solid tumor-directed CAR T cells available for tumor infiltration without the need for lymphodepletion. In immunocompetent C57BL/6 mouse models of pancreatic ductal adenocarcinoma and melanoma, these dual-targeted CAR T cells demonstrated enhanced peripheral expansion, improved anti-tumor efficacy, and increased survival without added dysfunction or toxicity compared to single antigen-targeted CAR T cells. We translated our findings to human CAR T cells by developing a pancreatic/xenograft model with CD19 + B cells in the periphery and again demonstrated that treatment with dual CAR T cells showed significantly enhanced tumor clearance and survival compared to single antigen-targeted CAR T cells. In conclusion, we demonstrate that dual-targeted CAR T cells boost peripheral expansion, and anti-tumor efficacy, providing a strategy for enhancing outcomes for patients treated with clinical CAR T products targeting solid tumors.